Occurrence of antibiotic resistance genes in extracellular and intracellular DNA from sediments collected from two types of aquaculture farms. (November 2019) - Yuan, Ke; Wang, Xiaowei; Chen, Xin; Zhao, Zhiqiang; Fang, Ling; Chen, Baoying; Jiang, Jie; Luan, Tiangang; Chen, Baowei
Abstract: The occurrence and quantities of ARGs in extracellular and intracellular DNA (eARGs and iARGs) from sediments collected in two different types of aquaculture farms were investigated. A total of 20 ARG subtypes associated with 7 categories of commonly used antibiotics (e.g., aminoglycosides, beta -lactams, sulfonamides, tetracyclines) were identified, and some of these subtypes were not related to the antibiotics used. ARGs are mainly present in the iDNA form with the ratio of the total iARGs to eARGs being in the range of 7.9–45.5. The ratio of eARG to iARGs varies greatly with ARG subtypes, probably due to their differences in persistence as a part of eDNA. Significant correlation between int 1 and ARGs was observed for both eDNA and iDNA in sediments from the aquaculture farms. Moreover, ARG pollution was more serious in bullfrog ponds than polyculture ponds due to the more frequent use of antibiotics in bullfrog rearing operations. Graphical abstract: Image 1 Highlights: ARGs could be detected in both extracellular and intracellular DNA from sediments. ARGs are mainly present in intracellular DNA in terms of diversity and levels. Significant correlation between int 1 and ARGs was observed for both eDNA and iDNA. ARG pollution was more serious in bullfrog farms than in polyculture ponds.